2021
DOI: 10.3390/tropicalmed6030120
|View full text |Cite
|
Sign up to set email alerts
|

Lopinavir and Nelfinavir Induce the Accumulation of Crystalloid Lipid Inclusions within the Reservosomes of Trypanosoma cruzi and Inhibit Both Aspartyl-Type Peptidase and Cruzipain Activities Detected in These Crucial Organelles

Abstract: Several research groups have explored the repositioning of human immunodeficiency virus aspartyl peptidase inhibitors (HIV-PIs) on opportunistic infections caused by bacteria, fungi and protozoa. In Trypanosoma cruzi, HIV-PIs have a high impact on parasite viability, and one of the main alterations promoted by this treatment is the imbalance in the parasite’s lipid metabolism. However, the reasons behind this phenomenon are unknown. In the present work, we observed by transmission electron microscopy (TEM) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…Lopinavir exhibited an inhibition of growth of some fungal cells and has potential effect as a therapy for fungal infections [ 8 , 9 ]. In addition, lopinavir has been investigated as a treatment plan for some parasitic infections [ 10 , 11 ]. Recently, Lopinavir has been evaluated alone or in combination with ritonavir in the treatment of COVID patients, but limited success has been shown [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…Lopinavir exhibited an inhibition of growth of some fungal cells and has potential effect as a therapy for fungal infections [ 8 , 9 ]. In addition, lopinavir has been investigated as a treatment plan for some parasitic infections [ 10 , 11 ]. Recently, Lopinavir has been evaluated alone or in combination with ritonavir in the treatment of COVID patients, but limited success has been shown [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Pereira et al, the cultivation of epimastigotes with a medium supplemented with 50% fetal calf serum caused the formation of lipid inclusions of different shapes in the reservosomes 15 . The accumulation www.nature.com/scientificreports/ of lipid content leading to the deformation of reservosomes on Y strain epimastigotes was also caused by treatment with lopinavir and nelfinavir, which promote an imbalance in proteolysis and lipid storage, and might inhibit parasite aspartyl peptidases 22 . Several authors have also reported disorganization of reservosomes due to different drug treatments.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pereira et al 2011, the cultivation of epimastigotes with a medium supplemented with 50% fetal calf serum caused the formation of lipid inclusions of different shapes in the reservosomes 23 . The accumulation of lipid content leading to the deformation of reservosomes on Y strain epimastigotes was also caused by treatment with lopinavir and nel navir 24 .…”
Section: Discussionmentioning
confidence: 99%